Pendeteksian Kondisi Hardisk Menggunakan Software Hd Tune Pro 5.75 - Ikhsan Parinduri; Siti Nurhabibah Hutagalung (JURIKOM (Jurnal Riset Komputer), 2019)
Utilization of HD Tune Pro software 5.75. Benchmark features are very helpful in reading the accuracy of data about the good and bad quality of the existing system, clearly visible with the graph display and hard drive performance values used. The display system reads the accuracy of the data in MB / s and KB / s units. The feasibility of using the hard drive from the existing performance on the hard drive, the amount of data transfer, temperature, data reading access